Breve relato: a análise salivar antioxidante revela perfis distintos de acordo com os subtipos moleculares do câncer de mama - Mezoni, Mariane Fontana (2024)
Breast cancer is a heterogeneous and complex disease, with distinct biological subtypes and several risk factors involved. Therefore, the search for methods to investigate breast cancer biomarkers is constant. In this context, saliva constitutes a promising indicator of health not only oral, but also systemic, providing a quick and non-invasive disease status. Considering the role of antioxidants in the genesis and progression of breast cancer, the use of saliva to assess the patient's antioxidant capacity may represent a relevant strategy. Therefore, this study aimed to investigate the antioxidant capacity of saliva samples from patients with breast cancer and its correlation with the clinical aspects that determine the prognosis of the disease. This is an analytical observational, mixed (prospective and retrospective) cohort study, which included women with breast cancer treated at the Hospital do Câncer de Francisco Beltrão-PR (CEONC) from 2017 to 2022 and approved by the Institutional Ethics Committee under number CAAE 35524814.4.0000.0107. Saliva samples were selected from 134 volunteer patients diagnosed with breast cancer. Clinicopathological data were collected from the medical records of all participants. The assessment of total antioxidant capacity (TRAP) was carried out using the high-sensitivity chemiluminescence technique and statistical analyzes were conducted using Graphpad Prism version 9.0 software. We observed significantly reduced salivary TRAP levels in women with tumors positive for estrogen and progesterone receptors (p<0.05). An increase in salivary TRAP was also observed in patients with triple-negative tumors (p=0,041). No significant changes were observed in other clinical comparisons. Moderate correlations were observed between reduced salivary TRAP levels and the presence of estrogen receptors (R= -0.1881) and the presence of progesterone receptors (R= - 0.1837). Positive correlations were observed between TRAP levels and the expression of the ki67 proliferation index above 14% (R= 0.1697) and with the presence of the triple negative tumor molecular subtype (R= 0.2078). Correlation analysis of TRAP levels in saliva and blood demonstrated that there is no correspondence between them, and that TRAP levels in blood are often higher than those detected in saliva. These findings suggest salivary levels of TRAP as a possible systemic marker associated with the occurrence of breast cancer with clinical characteristics of worse prognosis such as triple-negative tumors and a high proliferation index.